2017
DOI: 10.1016/j.procbio.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosyl-l-methionine production by Saccharomyces cerevisiae SAM 0801 using dl-methionine mixture: From laboratory to pilot scale

Abstract: This study sought to develop a cost-effective biological catalysis process for S-adenosyl-L-methionine (SAM) production. During the process, a mixture of D-methionine (D-Met) and L-methionine (L-Met), namely DL-Met, was used as substrate to replace the conventional but expensive pure L-Met. The concentration of DL-Met in substrate was optimized. When 80 g/L of DL-Met was added in a 5 L-scale bioreactor, 13.74 g/L of SAM was produced with an L-Met conversion rate of 32.15%. The fermentation process was then sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Consequently, methionine is usually added directly into the medium as a fermentation substrate to produce SAM and various previous studies have aimed to improve SAM production from methionine, including fermentation optimization, conventional mutation breeding, and genetic engineering [7, 14]. The conversion rate from expensive methionine to SAM ranges from 15 to 42% [1517], resulting in high cost. Therefore, development of efficient SAM production methods using methionine-free medium is much needed.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, methionine is usually added directly into the medium as a fermentation substrate to produce SAM and various previous studies have aimed to improve SAM production from methionine, including fermentation optimization, conventional mutation breeding, and genetic engineering [7, 14]. The conversion rate from expensive methionine to SAM ranges from 15 to 42% [1517], resulting in high cost. Therefore, development of efficient SAM production methods using methionine-free medium is much needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although l ‐methionine was often fed for SAM biosynthesis in yeast (Kanai, Mizunuma, Fujii, & Iefuji, ; Ren et al, ), dl ‐methionine should be a more suitable substrate for industrial SAM production, due to the much lower cost. As l ‐methionine is the specific substrate of SAM synthetase, d ‐methionine was wasted and even resulted in toxicity to yeast cells (Rytka, ; Yow et al, ; Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the strains using l ‐methionine as the substrate, the recombinant strain HDL‐R2 showed comparable SAM production by feeding cheaper dl ‐methionine. Ren et al () reported that 10.2 g/L SAM with a content of 78.2 mg/g DCW was accumulated in an industrial S. cerevisiae SAM0801 by feeding 40 g/L dl ‐methionine, while 10.9 g/L SAM with a content of 78.9 mg/g DCW was obtained by feeding 20 g/L l ‐methionine, suggesting that d ‐methionine was not converted to l ‐methionine in vivo. To the best of our knowledge, it was the first time to engineer S. cerevisiae for efficient SAM production from low‐cost dl ‐methionine via the conversion of d ‐methionine to l ‐methionine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy adopted was increment of intracellular l ‐Met levels and redirection of methionine to SAM biosynthesis, such as optimization of the l ‐Met feeding in an engineered P . pastoris strain (Hu et al, 2009b) and using dl ‐Met (a mixture of d ‐Met and l ‐Met) as a substrate for SAM production in a mutant Saccharomyces cerevisiae (Ren et al, 2017). In fact, it is essential to optimize culture conditions for a newly constructed strain, since physiological characteristics are strain/clone specific and not predictable a priori.…”
Section: Introductionmentioning
confidence: 99%